Comparison of Tourism and Hospitality Industry Financial Performance Before and After COVID-19: A Systematic Literature Review - Nurwitasari, Ayu; Waspada, Ikaputera; Sari, Maya (Politeknik Pariwisata NHI Bandung, 2023)
Purpose of the study: The COVID-19 pandemic has made the tourism sector unstable, where during the COVID-19 pandemic, the tourism industry faced several risks such as decreased revenue and operating profits, this decline certainly affected the company's financial performance. This study aims to explore and describe the trends and evolution of the latest academic literature on the financial performance of the tourism industry before and after the COVID-19 pandemic which were published as relevant articles. Design/methodology: This study uses the concept of literature review using the Systematic Literature Review (SLR) technique. The Systematic Literature Review technique is an important feature of academic research. By summarizing, analyzing, and synthesizing a group of related literature, can test certain hypotheses and/or develop new theories. Findings: The results of the study show that the financial performance of the tourism industry before and after COVID-19 is dominant using profitability ratio measurements. Research limitations/Implications: One limitation of this study is the reliance on secondary data sources for the literature review. As the study uses the Systematic Literature Review (SLR) technique, it may be limited by the availability and quality of existing literature on the financial performance of the tourism industry before and after the COVID-19 pandemic. Novelty/Originality of the study: This research can be used as material for consideration for conducting further research on the financial performance using activity ratios and market ratios.